The Influence of Competence and Motivation on Teacher Performance at Mekarwangi Lembang High - Aryatie, Yayah; Avianti, Widiya; Mulyana, Agus (Siber Journal of Advanced Multidisciplinary, 2024)
The purpose of this study was to analyze “The Effect of Teachers” Performance at SMA Mekarwangi Lembang in West Bandung Regency” the number of samples used in the study were 33 teachers. The researchmethode used was the Descriptive Method (Descriptive Survey) and the Verification Method (Verification Survey). The Results of the analysis and discussion showed that the Competency Variables (X1) of the Teachers of SMA Mekarwangi Lembang High school in West Bandung Regency are in the good category, but there were still weak aspects namely the teacher does not have a hefty character and easily deterred nature and it can be influenced by negative circumstances challenges in all situations and then teachers should look neat, polite also in accordance with the rules made and agreed by the school. Motivation Variables (X2), the teachers of Mekarwangi Lembang in West Bandung Regency are in the good category, however there were still some week aspects, namely work motivation appeard because of a strong urge to find positions in groups and in achieving predetermined target, while variabels Teacher Performance (Y) in SMA Mekarwangi Lembang West Bandung Regency was in the good category, however there were still weak aspects, namely having initiatives that are useful in helping to solve better and skilled work in comepleting work competencies that must be in the teacher, inpluential to word the performance off teachers at SMA Mekarwangi lembang in west Bandung Regency, this means that the more competencies possessed by the teacher is good, the beatheer the teacher’s performance on the contrary the lower the competency the teacher has, the teacher’s performance is getting weak. Teachers work’s motivation influenced the teachers ferpormens at SMA Mekarwangi Lembang West Bandung Regency. This means that the more the teacher work motivation is high, the better the teacher’s performance on the contrary the lower the motivation off the teacher’s work, the teacher performance is getting weak. There was signifcance simultaneously competency effect thet is owned by the teacher and the teachers’ work motivation, the teacher’s performance is getting better as always Conversely the lower the competence and motivation of the teacher’s work, the teacher’s performance is getting weak. Based on the finding of the research above, the researcher provided the following suggestions: 1. For teachers that should the competencies that have been owned be the main capital in teaching so that students are fulfilled their rights to learn according to the competencies that are in demand, and existing motivation is further strengthened to obtain better performance in achieving the goals to be accomplished. 2. To Principal that should be more nurturing with teacher supervision periodically soi that it can be monitored properly and provide a good stimulus to teachers in the form of reward and punishment in the form of periodic salary increases, additional structural positions, and more educating punishment to further improve the quality of teacher’s.